The Essence of Repentance in Qs. Az-Zumar: 54 (Study of Analysis of Tafsir Ruh al-Ma'ani By al-Alusi) - Nisfa Fauziah El Sanda; Fauzi Fathur Rosi (Tilawah: Journal of Al-Qur'an Studies, 2025)
In life, humans must never escape from mistakes, especially Muslims. The Qur'an should be the main foundation in all walks of life and be a guide in every matter and problem, including in achieving repentance to Allah SWT. However, there are many factors that can mislead humans, lead to the wrong path and tempt humans to follow temptations, lusts that can lead to sin, especially in a life that is increasingly deviating from Islamic teachings. The result can destroy man and prevent him from doing good. Therefore, it is necessary for humans to refer to the Qur'an as a helper to get an understanding of asking for forgiveness for the sins that have been committed through repentance. Based on the context of the research, there are two main focuses discussed in this research, namely: 1). What is the meaning of repentance according to Al-Alusi in Ruh Al-Ma'ani interpretation? 2). How is the essence of repentance in QS Az-Zumar: 54 Al-Alusi's perspective in Ruh Al-Ma'ani interpretation? the focus of the research is Al-Alusi's interpretation of the Nature of Repentance in QS. Az-Zumar: 54.This type of research is included in library research, an analytical study with a qualitative approach. This research also uses thematic interpretation, the primary data source is the book of Tafsir Ruh Al-Ma'ani by Al-Alusi. The results of the findings in this study, etymologically the meaning of repentance in Al-Alusi's view is to return from sin to obedience to Allah, while terminologically repentance is a way to return to Allah SWT, not just the elimination of sins but also the establishment of a better relationship with Allah SWT. While the essence of repentance contained in QS Az-Zumar: 54 Al-Alusi's perspective in the Ruh Al-Ma'ani interpretation is the process of returning to Allah SWT with sincerity before it is too late, because it is driven by love and awareness of the greatness of Allah SWT, not just fear.